2020
DOI: 10.1021/acs.analchem.0c02830
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Liquid Microjunction Extraction for Profiling Neuronal RNA Modifications by Liquid Chromatography–Tandem Mass Spectrometry

Abstract: RNA modifications are emerging as critical players in the spatiotemporal regulation of gene expression. Although liquid chromatography-tandem mass spectrometry (LC-MS/MS) enables the simultaneous quantification of numerous enzymatically modified RNAs in a biological sample, conventional RNA extraction and enzymatic digestion protocols that are employed prior to analysis have precluded the application of this technique for small-volume samples. In this study, a biphasic liquid microjunction (LMJ) extraction sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Gradient elution and MS were performed, as previously described. 33,34 Data Analysis. Modified nucleosides were identified by comparing MS2 spectra and LC retention characteristics to database values.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gradient elution and MS were performed, as previously described. 33,34 Data Analysis. Modified nucleosides were identified by comparing MS2 spectra and LC retention characteristics to database values.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…30−32 We recently developed an LC−MS-based method optimized for CNS tissues in the neurobiological model animal, Aplysia californica. 33 Using this approach, we found that a nonassociative learning paradigm in A. californica produced timedependent shifts in neuronal RNA modification profiles across CNS subregions (i.e., major ganglia). 34 These characteristic changes in neuronal RNA modifications contributed to increased synthesis of poly-glutamine proteins and neuron excitability, reinforcing the functional role of multiple RNA modifications in CNS plasticity.…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This landscape, or “epitranscriptome,” is responsive to external stimuli and is involved in regulating translation during heat shock [ 7 ], oxidative stress [ 8 ], methylation stress [ 9 ], and experience-dependent plasticity in the central nervous system [ 10 , 11 , 12 ]. Dramatic variations in RNA modification identity and abundance have also been characterized in small clusters of cells and even single cells [ 13 , 14 , 15 , 16 ], further driving the demand for methods that are capable of rapidly characterizing and quantifying modified RNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrate that non-associative learning in Aplysia coincides with characteristic time- and region-dependent rearrangements of neuronal RNA modification profiles. Using a liquid chromatography (LC)–tandem mass spectrometry (MS/MS) approach optimized for RNA modifications, 41 we identified higher levels of 7-methylguanosine (m 7 G) in total RNA extracts as well as 1-methyladenosine (m 1 A) and 5-methoxycarbonylmethyl-2-thiouridine (mcm 5 s 2 U) in tRNA during behavioral sensitization of the tail-elicited siphon withdrawal reflex (TSWR). Treatment of ganglia with mcm 5 s 2 U-rich tRNA isolated from sensitized donors increased levels of poly-Q proteins and produced electrophysiological hallmarks of increased excitability in neurons.…”
Section: Introductionmentioning
confidence: 99%